Strategi Bertahan Hidup Korban PHK Masa Pandemi Covid-19 di Desa Tejakula, Buleleng, Bali - Kamajaya, Gede; Nugroho, Wahyu Budi (Jurnal Community, 2024)
There are 46,000 employees who have experienced layoffs due to the Covid-19 pandemic in Bali. Of the many workers who were laid off, 652 of them were residents of Tejakula Village, Buleleng, Bali. This condition forces them to choose to return to their hometowns while there are not enough job opportunities in their hometowns. Based on the conditions above, this research attempts to answer the question What are the survival strategies for layoff victims during the Covid-19 pandemic in Tejakula Village, Buleleng, Bali by using a survival strategy theory analysis knife which is divided into three main strategies. To obtain the data mentioned above, the data in this research follows the principles of qualitative research methods where the data is presented in descriptive narrative form whose data sources come from interviews, literature studies and field observations. In general, the victims' survival strategies Termination of employment during the Covid-19 pandemic in Tejakula Village can be categorized into three forms: 1) Active strategy, 2). Passive strategy, 3). Network strategy. The important aim of this research is to obtain an overview of the survival strategies of victims of layoffs during the Covid-19 pandemic in Tejakula Village. At the same time, the results of this research are expected to provide theoretical implications for future Bali policy formulation so that they are not completely dependent on the tourism sector but can see the potential for home-based MSMEs is mainly in the food and beverage sector with potential.